PENGARUH LINGKUNGAN KERJA FISIK DAN NON FISIK TERHADAP PRODUKTIVITAS PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PIDIE - Muhammad Nur; Husaini Abdullah; Cut Putri Laila Kusuma (Jurnal Sains Riset, 2022)
This study aims to determine "The Influence of the Physical and Non-Physical Work Environment on Employee Work Productivity at the Population and Civil Registration Service in Pidie Regency". Where the independent variables are the physical work environment (X1) and non-physical (X2), and employee productivity (Y) as the dependent variable. employees who work at the Population and Civil Registration Office of Pidie Regency, both permanent employees and contract employees, which total 65 employees. The entire population in this study was taken as a sample using the Convinience Sampling technique. This analysis includes validity test, reliability test, multiple regression analysis classical assumption test, hypothesis test through F test and t test, and analysis of the coefficient of determination (R²). Y = 4.801 + 0.390 X1 + 0.428 X2. Based on the results of the analysis above, it can be concluded that of the two variables studied, it turns out that the non-physical work environment variable (X2) has the most dominant influence of 42.8% on work productivity (Y) at the Pidie Regency Population and Civil Registration Office. The relationship between the dependent and independent variables, namely each variable Physical work environment (X1) and Non-physical (X2) Work productivity (Y) Population and Civil Registration Office of Pidie Regency with a correlation index of 0.902% This means that the relationship is very strong.Keywords: Physical Work Environment, Non-Physical, Employee Productivity